Asymmetrisch-Selektive Polymerisation von Nicht-Olefinischen Monomeren - H.G. Bührer (CHIMIA)
Among the various methods of preparing optically active polymers the so-called asymmetric-selective (stereoelective) polymerization of racemic monomers is particularly attractive. Racemic compounds such as propylene oxide, propylene sulfide and α-amino acid NCA have thus been polymerized with optically active initiators to high-molecular weight optically active polymers. The interrelations between the structures of monomer and initiator on the one hand, and the stereoelectivity of the process on the other are discussed, together with some quantitative models. For highly stereoelective systems, e. g. propylene sulfide / ZnEt2 / optically active α-glycol, this type of polymerization is also an elegant way of separating racemic mixtures kinetically.